Preparing Teachers and Administrators for the Field of Religious Education - McBride, Alfred A. (Horizons, 1976)
A considerable complexity surrounds the preparation of teachers and administrators for the field of religious education. If it's teachers you are thinking of, then you must determine which level of teaching you will be preparing them for: Primary, Intermediate, Junior High, High School, College, Adult. (6 levels)As for administrators there are five constituencies out there: Chairpersons of religion departments in elementary schools, high schools, colleges, Parish Directors or Coordinators, Diocesan Directors.Certain essentials will be necessary for everyone. Religious content such as Bible, theology, liturgy. Humanistic content such as behavioral science (counseling, developmental, behaviorist psychology and religious sociology), educational theory, some poetry and film study, administrative theory (Barnard and Brucker)—this last, of course, only for administrators—and lastly, method.Most teachers and administrators are receiving plenty of religious content, a fair amount of behavioral science, not too much educational theory, practically no management skills, and virtually no method.From what I can see, the weakest parts of college and graduate school preparation programs are in the area of management theory and practical educational method. It is to this question of method I wish to direct my remarks.Prior to launching directly into the topic I want to note that a consciousness of Parish Community should be uppermost in these varying preparations. The territorial parish, for the foreseeable future, will be the basic unit of Catholic Church life. It is the fundamental structure wherein most religious teaching and administrating will go on.